Assessment of Transition Element Speciation in Glasses Using a Portable Transmission Ultraviolet–Visible–Near-Infrared (UV-Vis-NIR) Spectrometer. Issue 5 (May 2016) - Hunault, Myrtille; Lelong, Gérald; Gauthier, Michel; Gélébart, Frédéric; Ismael, Saindou; Galoisy, Laurence; Bauchau, Fanny; Loisel, Claudine; Calas, Georges
A new low-cost experimental setup based on two compact dispersive optical spectrometers has been developed to measure optical absorption transmission spectra over the 350–2500 nm energy range. We demonstrate how near-infrared (NIR) data are essential to identify the coloring species in addition to ultraviolet visible data. After calibration with reference glasses, the use of an original sample stage that maintains the window panel in the vertical position enables the comparison of ancient and modern glasses embedded in a panel from the Sainte-Chapelle of Paris, without any sampling. The spectral resolution enables to observe fine resonances arising in the absorption bands of Cr 3+, and the complementary information obtained in the NIR enables to determine the contribution of Fe 2+, a key indicator of glassmaking conditions.